1992
DOI: 10.1093/oxfordjournals.humrep.a137719
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy achieved by transferring blastocysts into endometrial stroma in mice

Abstract: To prevent the extra-uterine discharge of transferred embryos, we directly inserted mouse embryos into the endometrial stroma (intra-endometrial embryo transfer). A 27G injection needle was inserted near the utero-tubal junction into the endometrial stroma. After removal of the needle, a glass micropipette was inserted and one embryo was transferred with a very small amount of culture medium. To determine the feasibility of this method, the uterine lumen was flushed with phosphate-buffered saline from the tuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Some of these functions include serving as a growth factor, activation/inactivation of transcription factors, inhibition of apotosis and protein refolding [118,121,132]. Selenium (Se) is a trace element whose role in mammalian biochemistry was described in 1957.…”
Section: Cooselenocysteinementioning
confidence: 99%
“…Some of these functions include serving as a growth factor, activation/inactivation of transcription factors, inhibition of apotosis and protein refolding [118,121,132]. Selenium (Se) is a trace element whose role in mammalian biochemistry was described in 1957.…”
Section: Cooselenocysteinementioning
confidence: 99%
“…injection of PMSG (5 IU), and then at 1700 h on day 23, hCG (5 IU) was ip. injected to induce ovulation as described [12]. The same experiments were performed five times under each stress condition, respectively.…”
Section: Stress Conditionsmentioning
confidence: 99%
“…It is also not known whether an embryo transferred under luminal epi thelium is able to develop normally and whether it is pos sible to increase pregnancy rate by assisted implantation. In the mouse, pregnancies were achieved by transferring blastocysts into the endometrial stroma [6], By using this technique it was possible to increase pregnancy and em bryonic viability rates in asynchronous embryo transfer in the mouse [7], Implantation of human embryos involves integrated series of processes including adhesion to the endometrial mucosa and invasion of the blastocyst through the lumi nal epithelium into the endometrial stroma [8]. Bulletti et al [9] injected human blastocysts into the endometrium of human ex vivo perfused uteri and demonstrated that blastocysts can successfully undergo implantation and trophoblastic invasion during 52 h of extracorporeal per fusion.…”
Section: Introductionmentioning
confidence: 99%